Current knowledge on the application of membrane-based technologies for the removal of cytostatics from water. (June 2022) - Gouveia, Teresa I.A.; Garcia-Costa, Alicia L.; Alves, Arminda; Santos, Mónica S.F.
Abstract: Cytostatics are a class of pharmaceuticals of major concern due to their increasing consumption in cancer therapy, their resistance to conventional wastewater treatment processes and their potential carcinogenicity to any eukaryotic organism. The ubiquitous presence of cytostatics on effluents from wastewater treatment plants and natural water streams has raised concerns about environmental integrity, resilience and sustainability. Therefore, the seeking for a treatment solution to mitigate their entrance, spread and accumulation in the environment is urgent. Besides the well-known tertiary treatments of sorption by activated carbon or even more recent ones such as ozonation, membrane processes are advanced treatment technologies with high potential benefits, since they are known to provide high removal rates for low molecular weight organic pollutants and effluents of excellent quality. For the first time, this work intends to provide a comprehensive literature review on the application of membrane-based processes (as stand-alone units or combined with other technologies) for the treatment of wastewaters and waters contaminated with cytostatics. Information on the influence of operating conditions on process efficiency, removal mechanisms and toxicity of the generated effluents are discussed in detail, while the current gaps are highlighted. Furthermore, relevant information regarding the implementation of membrane technologies for cytostatics depletion, from an economical and environmental perspective, is given at first hand.